Associations between objective measures of performance-related characteristics and perceived stress in young cross-country skiers during pre-season training - Mishica, C.; Kyröläinen, H.; Taskinen, S.; Hynynen, E.; Nummela, A.; Holmberg, H.-C.; Linnamo, V. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Monitoring the performance-related characteristics of athletes can reveal changes that motivate adaptation of training that cannot only improve performance, but also reduce the risk of injury, illness and overtraining 1. Here, we examine the relationships between changes in submaximal running, maximal jump performance (CMJ), concentrations of blood lactate, sleep duration (SD) and latency (SL), and perceived level of stress (PSS) in junior cross-country skiers during a pre-season training period.